Mechanical Behaviors of Friction Stir Spot Welded Joints of Dissimilar Ferrous Alloys under Opening-Dominant Combined Loads - Md. Abu Mowazzem Hossain; Md. Tariqul Hasan; Sung-Tae Hong; Michael Miles; Hoon-Hwe Cho; Heung Nam Han (Advances in Materials Science and Engineering)
Mechanical properties and failure behaviors of friction stir spot welded (FSSW) joints of two dissimilar ferrous alloys, cold-rolled carbon steel (SPCC) and 409L stainless steel (SUS 409L), are investigated under opening-dominant combined loads. The texture of dissimilar FSSW joints depends on the upper sheet material. The failure contours for the FSSW joints under combined loads are constructed in terms of the axial load and shear load by modifying existing failure criteria for resistance spot welds. The shape of the failure contour also depends on the upper sheet material. The failure contours are nearly elliptic in shape when the upper sheet is SPCC and are relatively straight lines when the upper sheet is SUS 409L.